Preferences for the shared use of electric-powered vehicles in mobility packages: an empirical analysis of MaaS in a university context - Decker, Lea; Marx, Christian P.; Weiβ, Matthias; Werbeck, Nicola (Frontiers in Environmental Economics, 2023)
Previous research on preferences of potential Mobility-as-a-Service (MaaS) users often included public transport (PT) in bundled mobility options. Due to the often-reported enormous importance of PT availability, including PT in those bundles may have led to distortions in identifying other vehicle preferences in MaaS offerings. With our analysis we counteract this distortion and investigate how other means of transport are evaluated in mobility packages when PT is not part of the package, but at the same time access to PT is not completely excluded. We included electric-powered mobility alternatives of small significance or that past research had not considered at all, to find out which alternatives to or complements for PT users would prefer and might increase their approval of MaaS offerings. Furthermore, results in the existing literature are inconsistent in emphasizing whether sustainability and environmental protection are actually relevant in the valuation of different mobility options. Our analysis thus aims at identifying which electric-powered vehicles are preferred in a mobility package, when PT is not included and at investigating whether components concerning sustainability of a mobility package influences the preference structure of individuals. We based the empirical evaluation on a ranked-ordered conjoint analysis, ordering mobility packages by individual user preferences that operationalized and directly included sustainability. Thus, we conducted a study that identified vehicle preferences other than PT and the valuation of sustainability aspects in mobility patterns. The study further focused on a specific target group rarely considered in the context of analyzing MaaS preferences yet. We surveyed 995 students to identify preferences and willingness to pay (WTP) for MaaS among the very specific user group of students in Germany. Results of the empirical analysis show that a preference for an e-car and an e-scooter exists among the sample. Furthermore, we found evidence that sustainability plays a role in the evaluation of mobility packages. Accordingly, we determined that a potential decrease of emissions leads to a higher approval of MaaS. Our findings thus extend the theoretical and empirical understanding of preference-ordering of MaaS packages and clarifies the importance of sustainability in transportation mode choices.